The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1108/eum0000000002577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Store Music on Shopping Behavior

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
220
0
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(246 citation statements)
references
References 0 publications
12
220
0
14
Order By: Relevance
“…They suggested that the dominance variable might need reconceptualizing in terms of the perceived "persuasiveness" of the store atmosphere. However, they argued that this would make dominance variable more cognitive and less of a purely emotional state than the (Milliman 1982;Yalch and Spangenberg 1990). …”
Section: Marketing and Mehrabian-russell Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that the dominance variable might need reconceptualizing in terms of the perceived "persuasiveness" of the store atmosphere. However, they argued that this would make dominance variable more cognitive and less of a purely emotional state than the (Milliman 1982;Yalch and Spangenberg 1990). …”
Section: Marketing and Mehrabian-russell Theorymentioning
confidence: 99%
“…Research on elements of the store environment are multifarious; researchers have investigated the impact of music (Areni and Kim 1993;Hui, Dube and Chebat 1997;Milliman 1982;Yalch and Spangenberg 1990), color (Bellizzi, Crowley, and Hasty 1983), scent (Spangenberg, Crowley, and Henderson 1996), and crowding (Eroglu and Machleit 1990;Hui and Bateson 1991) as contributing factors to consumers' retail patronage. Combinations of store elements have also been investigated (Baker, Parasuraman, Grewal and Voss 2002;Eroglu, Machleit and Chebat 2005;Matilla and Wirtz 2001;Parasuraman, Grewal and Voss 2002), and include store atmospherics (Baker, Grewal and Parasuraman 1994;Donovan and Rossiter 1982;Iyer 1989;Park, Iyer and Smith 1989), store atmospherics triggering emotional reactions (Babin and Darden 1996;Baker, Levy and Grewal 1992;Darden and Babin 1994;Donovan et al 1994;Wakefield and Blodgett 1999), and store image (Korgaonkar, Lund, and Price 1985;Stanley and Sewall 1976;Steenkamp and Wedel 1991).…”
Section: Anova: Effect Of Cultural Elements Inmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, whether consumers like the genre of music being played can influence their shopping behaviors (Yalch and Spangenberg 1990). According to Herrington (1996), music preference and the liking of contextual features is a strong predictor of spending in service environments.…”
Section: Music's Added Valuementioning
confidence: 99%
“…The cognitive and affective responses are interdependent, and one may impact the other. Overall, positive sensations of the store design influenced consumers' willingness to stay longer and increased purchase intentions (Fiore, Yah, and Yoh 2000;Mattila and Wirtz 2001;Yalch and Spangenberg 1990).…”
Section: Servicescapementioning
confidence: 99%